Antibodies to Plasmodium vivax reticulocyte binding protein 2b are associated with protection against P. vivax malaria in populations living in low malaria transmission regions of Brazil and Thailand. - Wen-Qiang He; Stephan Karl; Michael T White; Wang Nguitragool; Wuelton Monteiro; Andrea Kuehn; Jakub Gruszczyk; Camila T França; Jetsumon Sattabongkot; Marcus V G Lacerda; Wai-Hong Tham; Ivo Mueller (Public Library of Science (PLoS), 2019)
Background The Plasmodium vivax Reticulocyte Binding Protein (PvRBP) family is involved in red blood cell recognition and members of this family are potential targets for antibodies that may block P. vivax invasion. To date, the acquisition of immunity against PvRBPs in low malaria transmission settings and in a broad age group of exposed individuals has not been investigated. Methodology/principal findings Total IgG antibody levels to six members of the PvRBP family (PvRBP1a, PvRBP1b, PvRBP2a, PvRBP2b, a non-binding fragment of PvRBP2c (PvRBP2cNB) and PvRBP2-P2) were measured in samples collected from individuals living in two regions of low P. vivax endemicity in Brazil and Thailand. In both settings, levels of total IgG to PvRBP1a, PvRBP2b, PvRBP2cNB, and PvRBP2P-2 increased significantly with age (rho = 0.17-0.49; P<0.001). IgG responses to PvRBP1a, PvRBP2b and PvRBP2cNB were significantly higher in infected individuals by using Wilcoxon's signed-rank test (P<0.001). Of the six PvRBPs examined, only antibodies to PvRBP2b were associated with protection against clinical malaria in both settings. Conclusion/significance Our results indicate that PvRBP2b warrants further preclinical development as a blood-stage vaccine candidate against P. vivax. Total IgG responses to PvRBPs were also shown to be promising immunological markers of exposure to P. vivax infection.